Use of FloSeal Sealant in the Surgical Management of Tubal Ectopic Pregnancy - Mara Clapp; Jaou-Chen Huang (Case Reports in Obstetrics and Gynecology)
Background. Surgery is sometimes required for the management of tubal ectopic pregnancies. Historically, surgeons used electrosurgery to obtain hemostasis. Topical hemostatic sealants, such as FloSeal, may decrease the reliance on electrosurgery and reduce thermal injury to the tissue. Case. A 33-year-old G1 P0 received methotrexate for a right tubal pregnancy. The patient became symptomatic six days later and underwent a laparoscopic right salpingotomy. After multiple unsuccessful attempts to obtain hemostasis with electrocoagulation, FloSeal was used and hemostasis was obtained. Six weeks later, a hysterosalpingogram (HSG) confirmed tubal patency. The patient subsequently had an intrauterine pregnancy. Conclusion. FloSeal helped to achieve hemostasis during a laparoscopic salpingotomy and preserve tubal patency. FloSeal is an effective alternative and adjunct to electrosurgery in the surgical management of tubal pregnancy.